Design of a monitor for the debugging and development of multiprocessing process control systems : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology in Computing Technology at Massey University - Dobbie, Gillian (Massey University, 1987)
This thesis describes the design of a general purpose tool for debugging and developing multimicroprocessor process control systems. With the decreasing pnce of computers, multimicroprocessors are increasingly being used for process control. However, the lack of published information on multiprocessing systems and distributed systems has meant that methodologies and tools for debugging and developing such systems have been slow to develop. The monitor designed here is system independent, a considerable advantage over other such tools that are currently available.
Keywords: Computer programs; Design; Process control; Testing; Debugging in computer science